PERSEPSI PENGUSAHA USAHA MIKRO KECIL DAN MENENGAH TERHADAP SERTIFIKASI HALAL DI KABUPATEN ROKAN HILIR - Usnan, Usnan (LPPM IAI Dar Aswaja Rokan Hilir, 2024)
The urgency of the halal certification program is to protect consumers, especially Muslims, from consuming prohibited products However, it has been revealed that there are still UMKM entrepreneurs in Rokan Hilir Regency who are unwilling to obtain halal certification This research uses a qualitative method with a case study approach, involving ten UMKM entrepreneurs as informants, seven of whom are located in Kota Bagansiapiapi and three in Kecamatan Kubu. Data is input through interviews accompanied by observation and documentation The research results indicate that the perception of small and medium-sized business owners in Rokan Hilir Regency towards halal certification is still not good This is revealed by four indicators that uncover perception variables, all of which point to a lack of understanding among small and medium-sized business owners who were used as sources in understanding the meaning, legal basis, procedures, and benefits of halal certification. The negative perception of MSME entrepreneurs towards halal certification is caused by factors such as lack of attention, interest, alignment of needs, and visible evidence from their environment The deficiency in these four factors leads MSME entrepreneurs to have a negative view when describing halal certification for their products Meanwhile, good physical or physiological health factors in MSME entrepreneurs cannot be utilized for managing halal certification.